The Role of Oxidative Stress In Lead Poisoning - Al-Ubaidy, Bashier; K. Al-Khashali, Dawsar; A. Numan, Nawfal (Iraqi Journal of Pharmaceutical Sciences, 2017)
To investigate the relationship between increased lipid peroxidation, and the lowering of both plasma total proteins and albumin in lead-exposed workers, and the effectiveness of antioxidants (vit. C and E) in modulating oxidative stress in those workers.Thirty male and females workers employed in the Iraqi storage battery (age range 20-40 years) were participating in this study. Additionally, 11 healthy subjects were served as healthy controls, with the same age range compared to workers group, to avoid the effects of age variations on the studied parameters. Blood lead levels, erythrocytes and plasma MDA, erythrocytes and plasma GSH, total protein and albumin levels in healthy controls and lead-exposed workers pre- and post-treatments with antioxidant were measured.Comparison with healthy control groups reveal 360% increase in blood lead levels, 150% increase in erythrocyte MDA, 117% increase in plasma MDA, 28% decrease in erythrocyte GSH, 56% decrease in plasma GSH, 13% decrease in total plasma protein and 23% decrease in albumin levels in lead-exposed workers. Treatment with a combination of antioxidant vitamins (1000 mg/day vit. C and 200 mg/day vit. E) for one month produced significant reduction 12% in lead levels, 54% in erythrocyte MDA, 53% in plasma MDA; significant increase 41% in erythrocyte GSH, 120% in plasma GSH and 11% in plasma albumin levels in comparison with pre-treatment levels.In conclusion, there is a beneficial effect of antioxidants on the oxidative stress parameters that not only related to their ability to remove lead from target cells, but also associated with antioxidant potential for bolstering thiol antioxidant capacity, and this makes these vitamins a good candidate for therapeutic intervention in lead poisoning.